Morphometric and Micrometrical Studies of the esophageal tonsil in Siruvidai Chicken of Tamil Nadu - P. Sridevi; Sabiha Hayath Basha; S. Usha Kumary; N. Pazhanivel; P. Veeramani (Indian Journal of Veterinary Anatomy, 2025)
The study aimed to investigate the morphometric and micrometric age-related changes in the esophageal tonsil of Siruvidai, a native chicken breed from Tamil Nadu. The tissue samples from six birds of each age group were collected from 4th week, 8th week, 12th week, 18th week, 24th week and 52nd weeks, respectively. Both male and female Siruvidai chicken were included in the study. The topography of the esophageal tonsil across all age groups was found to be similar. The esophageal tonsil had become more clearly visible from 8th week onwards and became distinct and more defined with the advancement of age. Statistical analysis of morphometrical data showed that esophageal tonsil reached to its maximum size by 18th weeks of age and remained constant in 24th and 52nd week of age. The micrometric measurements revealed that the lymphoid nodule of the esophageal tonsil also reached to its maximum diameter by 18th weeks , of age and gradually decreased during 24th and 52nd week of age.